BIFID XIPHISTERNUM -A RARE MORPHOLOGICAL VARIATION DURINGAUTOPSY - Duchania, Sunil Kumar; Chouksey, Vivek Kumar; Rani, Mukta; Rani, Yashoda (Journal of Forensic Medicine and Toxicology, 2018)
Objectives: A bifid sternum is a rare congenital anomaly generally diagnosed as asymptomatic at birth. However sometimes it may present as chance finding in adult life during the postmortem examination. This article  documents the occurrence of bifid xiphisternumduring autopsy which may be misleading and may result in serious erroneous conclusions, particularly when evaluating skeletonised human remains.Methods: Soft tissues removed from themacerated sterna by blunt dissection and the findings in xiphisternal endingrecorded.  Results: Out of total fifty sternum studied bifid xiphoid process was seen in only 5 (10% ) sternums. Of these, bifid process with joined ends was found in only one (2%) sternum and bifid process with unjoined xiphoid in four   (Figures 1 and 2) of the sterni. Elongated xiphisternum was found in only one of the cases (Figure 3), broad and thin in only one (2%) (Figure 4) whereas curved xiphoid was found in two of them.
Keywords: Bifid; xiphisternum; sternum; xiphoid process; congenital anomaly; morphological variation